The Correlation Between Employee’s Work Motivation and Their Interpersonal Communication on Work Effectiveness at PT. Pelindo Jasa Maritim - Fariza, Riska; Asfah, Indrawaty; Asriati; Azhari, Ahmad; Anantatama, Surya (Celebes Journal of Language Studies, 2024)
This research is a correlation quantitative research with a sample of 62 employees at PT. Pelindo Jasa Maritim Makassar. The employees were obtained using a simple random sampling. Data were collected using questionnaires and documentation. Data analysis was carried out with a description of the research data prerequisite test analysis, and hypothesis testing. The result showed that; (1) there is a positive significant relationship between work motivation and work effectiveness at PT Pelindo Jasa Maritim Makassar. This has been proven using the calculation of Pearson Product Moment. It was found that the correlation coefficient, a value of 0,406 is obtained. The level of the coefficient interval which is in the range of 0,400 – 0,599 shows a strong enough correlation level, (2) there is a positive significant relationship between interpersonal communication and work effectiveness at PT Pelindo Jasa Maritim, it was found that the correlation coefficient, a value of 0,671 is obtained and the level of the coefficient interval which is in the range of 0,600 – 0,799 shows a strong correlation level.